Discrimination of Panax ginseng from counterfeits using single nucleotide polymorphism: A focused review - Ying, Zheng; Awais, Muhammad; Akter, Reshmi; Xu, Fengjiao; Baik, Sul; Jung, Daehyo; Yang, Deok Chun; Kwak, Gi-Young; Wenying, You (Frontiers in Plant Science, 2022)
Discrimination of plant species, cultivars, and landraces is challenging because plants have high phenotypic and genotypic resemblance. Panax ginseng is commonly referred to as Korean ginseng, which contains saponins with high efficacy on cells, and has been reported to be worth billions in agroeconomic value. Korean ginseng’s increasing global agroeconomic value includes additional species and cultivars that are not Korean ginseng but have physical characteristics close to it. This almost unidentifiable physical characteristic of Korean ginseng-like species is discriminated via molecular markers. Single nucleotide polymorphism (SNP), found across the plant species in abundance, is a valuable tool in the molecular mapping of genes and distinguishing a plant species from adulterants. Differentiating the composition of genes in species is quite evident, but the varieties and landraces have fewer differences in addition to single nucleotide mismatch. Especially in the exon region, there exist both favorable and adverse effects on species. With the aforementioned ideas in discriminating ginseng based on molecular markers, SNP has proven reliable and convenient, with advanced markers available. This article provides the simplest cost-effective guidelines for experiments in a traditional laboratory setting to get hands-on SNP marker analysis. Hence, the current review provides detailed up-to-date information about the discrimination of Panax ginseng exclusively based on SNP adding with a straightforward method explained which can be followed to perform the analysis.